Comparison the Role of Some Novel Biomarkers in Predicting Diabetic Nephropathy Between Diabetic Type 2 and Chronic Kidney Diseases Patients in Kirkuk City - Omar Haitham Hadi, Firas Faris Riji, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes mellitus most dangerous metabolic disorder and have high morbidity and mortality complications, the most DM complication is diabetic nephropathy. Diabetic nephropathy( DN) is an irreversible progressive disorder characterized by increased urine albumin excretion and/or impaired GFR. DM causes about 50 % of kidndiseasesase. An increase in prevalence of diabetes is projected to lead to a significant increase in patients with end-stage renal disease (ESRD) requiring renal replacement therapy (RRT), and up to 50% of the dialysis population is diabetic. We study 30 Diabetic patients with Chronic kidney diseases with hemodialysis ,30 diabetic patient with chronic kidney disease with out hemodialysis , 15 patient with diabetes only , and 15 control group .we measured kidney injury molecule-1 , liver type fatty acid binding protein ,zinc alpha 2 glycoprotein , serum creatinine ,uric acid .blood urea and random blood sugar .results showed that highest KIM-1 concentration in diabetic nephropathy with hemodialysis group (2.325± 1.095) followed by control group (1.842 ±0.866 ab )and followed with diabetes group (1.572 ±0.752 b ) and lowest mean level was diabetic nephropathy without hemodialysis group (1.344 ±0.623 b ) with highly significant differences (p < 0.001) of KIM-1 among groups .The highest mean level of L-FABP was recorded in diabetic nephropathy with hemodialysis group (254.6 ± 29.6 a ) followed by the control group (235.8 ± 28.9) and followed by diabetic group ( 9210.3 ± 28.7 ab )and the lowest mean level was diabetic nephropathy without hemodialysis group (149.5 ±25.9 a) with significant difference (P<0.002) of L-FABP among groups .The study showed that the highest mean level of ZAG recorded in diabetic nephropathy with hemodialysis group (140.1 ± 23.6 a) followed by control group( 130.9 ±11.5 a)and the lowest mean level was in diabetes group (88.3 ± 14.0 b ) and diabetic nephropathy without hemodialysis group (87.4 ± 19.60 b ) respectively with highly significant difference (P<0.0003). Aims: Role of biomarkers (KIM-1, L-FABP, ZAG) in detection early development of diabetic nephropathy .Correlation between biomarkers (KIM-1, L-FABP, ZAG) and progression of diabetic nephropathy to end stage of renal disease .Estimate how much relationship between biomolecules (creatinine , urea and uric acid ) with diabetes and its complication Methodology :The study included 90 individuals from Kirkuk city / Blood sample collected from patient and analysis was conducted to estimate concentration using Enzyme Linked Immunosorbent Assay (ELISA),and biochemicals using spectrophotometers . Keywords: Diabetes, diabetic nephropathy , chronic kidney disease ,kidney biomarkers